LOMBALGIA EM GESTANTES: PREVALÊNCIA, CARACTERÍSTICAS E FATORES - Madeira, Hellyne Giselle Reis (2012)
During pregnancy the maternal organism undergoes a series of adjustments due to hormonal and biomechanical changes that may result in overload on lumbar muscles, leading to tension and the development of low back pain. Objectives: To evaluate the prevalence of low back pain among pregnant women attended at an outpatient obstetrics, as well as to characterize this symptom and identifying its possible triggers and aggravating factors. Methods: Participants were 269 pregnant women, from first to third trimester of pregnancy, attended the outpatient clinic of obstetrics at the University Hospital Maternal and Child Health, in San Luis (MA), from May 2010 to February 2011. The socio-demographic, obstetric characteristics of low back pain were obtained by a questionnaire with closed questions during the interview on this occasion used the visual analog pain scale to measure pain intensity and the Oswestry questionnaire (QIO ) and Rolland Morris (QRM) to assess disability. Results: The prevalence of low back pain was 196 (73%) with the following characteristics: "stabbing" (62/31, 6%) with irradiation (162/82, 6%), most often daily (105 / 53.5%), generally starting at night (83/42, 3%) as also was most intense (122 / 62.2%), lasting approximately 1 hour (73/37, 2%). Improves with rest (100/51, 0%) and worsened in the standing position or sitting for a long time (86/43, 9%) and housewives (85/43, 4%), the levels of disability, Most changes were mild to moderate. The variables urinary tract infection (p = 0.028) and the score of the Oswestry Index Questionnaire - QIO (p = 0.0001) showed significant association with the pain scale. Conclusions: The prevalence of back pain among pregnant women is high, with specific characteristics. The degree of disability becomes moderate, and this group, the presence of urinary infection and higher disability scores were associated with increased intensity of low back pain.